Parents' perception of their child's weight status and intention to intervene: A Western Australian cross-sectional population survey, 2009-12 - Merema, M.; Sullivan, D.; Pollard, Christina; Abraham, J.; Tomlin, S.; Radomiljac, A. (2015)
Objective: To report on parents' perceptions of their child's weight status and how the child's body mass index (BMI) is associated with parent intentions to change or maintain the child's weight. Methods: Estimates were derived via data collected from 4,437 parents from 2009 to 2012 as part of the Western Australian Health and Wellbeing Surveillance System. To measure weight perceptions, parents were asked, “Is your child underweight, normal weight, overweight or very overweight?” BMI values were also derived via parent-reported height and weight. Parent intentions were assessed by asking parents, “What are your intentions regarding your child's weight?” Results: Significantly fewer parents perceived their child as overweight (8.2%) or very overweight (0.2%) than was derived via parent-reported height and weight (16.3% and 5.8%, respectively). More than half the parents with children above or below the healthy BMI range reported an intention to “do nothing” about their child's weight (between 54.5% and 70.0%). Conclusions: A large proportion of Western Australian parents misjudge their child's weight status and the majority express no intention to help their child achieve a healthy weight. Implications: The results reinforce the importance of population-level, parent-focussed interventions targeting perceptions of children's weight and appropriate action.